Family and sport : Notable contributions to sociology - Ortiz, Steven M. (Research in the sociology of sport ;, 2023)
The institution of sport has pervasive roots that are steeped in patriarchy. Despite this tradition, sport is at the forefront in making us aware of personal and social issues in global societies. However, sociological attention to family and sport is long overdue and sorely needed. Providing timely knowledge and long-awaited insights into pressing issues, this volume of Research in the Sociology of Sport establishes family and sport as a clearly identified field of study within sociology. Focusing on how families participate in sport in global societies where traditional norms are rapidly evolving, this edited collection presents unique contributions to an under researched area of sociological inquiry. Offering a wide range of perspectives and a multidisciplinary approach, contributors provide applicable solutions to this sociological oversight, and nuanced scholarship that invites future consideration. Divided into three major sections, chapters explore traditional values that are actively challenged by both children and adults, examine the effects of cultural shifts on family relationships, and assess the patriarchal structure of sport participation in global societies. Highlighting the microlevel of the family to grapple with contemporary social issues at the macrolevel of society, Family and Sport: Notable Contributions to Sociology charts new territory to advance a valuable understanding of family and sport issues.